Tumor fluorescence and oxygenation monitoring during photodynamic therapy with chlorin e6 photosensitizer - Kanamat Efendiev; Polina Alekseeva; Kirill Linkov; Artem Shiryaev; Tatiana Pisareva; Aida Gilyadova; Igor Reshetov; Arina Voitova; Victor Loschenov (Photodiagnosis and Photodynamic Therapy)
Background: The study is aimed at developing a method for monitoring photodynamic therapy (PDT) of a tumor using chlorin-type photosensitizers (PSs). Lack of monitoring of chlorin e6 (Cе6) photobleaching, hemoglobin oxygenation and blood flow during light exposure can limit the PDT effectiveness. Materials and methods: Phototheranostics includes spectral-fluorescence diagnostics of Ce6 distribution in the NIR range and PDT with simultaneous assessment of hemoglobin oxygenation and tumor blood flow. Fluorescence diagnostics and PDT were performed using the single laser λexc=660 ± 5 nm. Results: Combined spectroscopic PDT monitoring method allowed simultaneous estimation of Ce6 photobleaching, hemoglobin oxygenation and tumor vascular thrombosis during PDT without interrupting the therapeutic light exposure. Conclusion: The developed method of tumor phototheranostics using chlorin-type PSs may make it possible to personalize the duration of therapeutic light exposure during PDT.